Stylistic Elements in Sita Ram Adhikari's "Night Queen" - Rai, Himal Ser; Rai, Manju (NPRC Journal of Multidisciplinary Research, 2025)
Background: Sita Ram Adhikari's poem "Night Queen" is essentially a lyric poem, which, though superficially a light ode to a night-blooming flower, works upon a very complex plane of spiritual and moral inquiry. The poem exists at an interesting juncture between nature poetry and devotional literature, inviting critical scrutiny of its stylistic craftsmanship to reveal its deeper thematic engagement. Objective: This analysis tries to deconstruct the stylistic and structural elements of the poem and show how Adhikari transforms a floral subject into a profound symbol of moral idealism. An attempt is made to articulate how the poem's form-diction, tone, and imagery-functions in steering the reader from aesthetic admiration to a yearning for ethical self-improvement. Methods: This study adopts a close reading methodology, drawing from practical criticism and stylistic analysis. The poem is read as an autonomous aesthetic unit, strictly in light of its inner-literary elements such as apostrophe, personification, symbolism, and rhetorical structure; this is supplemented by interpretive lenses from devotional and lyric poetry traditions. Analysis: The power of the poem results from its unremitting apostrophe, which makes it intimate and prayer-like. The Night Queen, as a figure of discipline and justice, becomes an icon through the mixture of romantic and devotional language. Crucial stylistic decisions-in particular, the juxtaposition of "bright" presence with "never cloudy" vision, and rhetorical questions deployed iteratively-are pointed to as pivotal in tracking the progress of the speaker from lover to supplicant, in search of moral guidance. Conclusion: The study concludes that “Night Queen” is essentially a poem of emulation, not merely appreciation. Its stylistic architecture is carefully designed to move from external observation to an internal plea for virtue, framing the act of worship as a pursuit of moral betterment. Implication: Such a poem suggests that a proper engagement with beauty is an ethical act, one that compels introspection and aspiration. It suggests that literature, even in its most condensed forms, can form a crucial medium for philosophical reflection and a guide for personal conduct.